North-West Mounted Police post at Carcross, Yukon Territory, approximately 1898 - Hegg, Eric A., 1867-1948 (1898)
Caption on image: "N.W.M.P Post Cariboo Crossing" Original photograph by Eric A. Hegg 3005; copied by Webster and Stevens 64.A